2011
DOI: 10.1021/ef200859d
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Iron Oxide with Alumina in a Composite Oxygen Carrier during the Production of Hydrogen by Chemical Looping

Abstract: Solid solutions of hematite (α-Fe2O3) and corundum (α-Al2O3) have been synthesized by coprecipitation. The resulting particles have been used as oxygen carriers for the production of hydrogen by chemical looping and characterized using X-ray diffraction (XRD), temperature programmed reduction (TPR), specific surface area measurements (BET), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDXS). The particles were repeatedly (i) reduced with, e.g., CO to, nominally, Fe, (ii) then o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 36 publications
11
93
2
Order By: Relevance
“…It is thermodynamically supported to generate FeAl 2 O 4 when Al 2 O 3 was involved in the reaction [42,43]. FeAl 2 O 4 was a little difficult to further reduce to Fe and Al 2 O 3 due to the relatively slow reaction rate [44,45]. The impact of FeAl 2 O 4 on system efficiency needs to be confirmed in future work.…”
Section: Characteristics Of Phase Distribution Of the Reduced Particlmentioning
confidence: 97%
“…It is thermodynamically supported to generate FeAl 2 O 4 when Al 2 O 3 was involved in the reaction [42,43]. FeAl 2 O 4 was a little difficult to further reduce to Fe and Al 2 O 3 due to the relatively slow reaction rate [44,45]. The impact of FeAl 2 O 4 on system efficiency needs to be confirmed in future work.…”
Section: Characteristics Of Phase Distribution Of the Reduced Particlmentioning
confidence: 97%
“…When sintered at 850°C, some weak diffraction peaks of FeAl 2 O 4 appeared. When the hot pressing temperature increased to 900°C, the intensity of FeAl 2 O 4 diffraction peaks slightly increased, which indicated that the crystalline degree of FeAl 2 O 4 obviously improved [10,12].…”
Section: Effect Of Hot Pressing Temperature On the Microstructure Andmentioning
confidence: 99%
“…Several transition metal oxides (e.g., those of copper, cobalt, iron, manganese, and nickel) have all been identified as promising oxygen carrier candidates due to their tendency to be easily reduced [4,5]. Fe 2 O 3 and CuO are among the most-investigated materials due to their low cost, but each has drawbacks that may limit their practical implementation at scale (e.g., low oxygen transport capacity of Fe 2 O 3 [6] and adverse environmental implications for CuO) [7]. Despite its higher cost, NiO is also considered a good oxygen carrier due to its high oxygen content and reactivity.…”
Section: Introductionmentioning
confidence: 99%